2000
DOI: 10.1128/jb.182.2.385-393.2000
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Aspects of the Structured Cell Population in a Swarming Colony of Proteus mirabilis

Abstract: Proteus mirabilis forms a concentric-ring colony by undergoing periodic swarming. A colony in the process of such synchronized expansion was examined for its internal population structure. In alternating phases, i.e., swarming (active migration) and consolidation (growth without colony perimeter expansion), phase-specific distribution of cells differing in length, in situ mobility, and migration ability on an agar medium were recognized. In the consolidation phase, the distribution of mobile cells was restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
80
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 27 publications
7
80
1
Order By: Relevance
“…Four isolates, 91 1 (Pm), 91 2 (Pm), 66 2 (Ph) and 66 5 (Pp), showed enhanced swarming motility than others ( Figure 4). To date, Pm is thought to be a strong swarmer cell among Proteus species and here two isolates, 91 1 and 91 2 , of Pm exhibited faster swarming ( Figure 4B,C) than other species resembling with other reports [28]. However, in this study we found an isolate of Ph (66 2 ) which showed strong swarming motility comparable to Pm (Figure 6 B,C,E).…”
Section: Kinetics Of Swarming Motilitycontrasting
confidence: 55%
“…Four isolates, 91 1 (Pm), 91 2 (Pm), 66 2 (Ph) and 66 5 (Pp), showed enhanced swarming motility than others ( Figure 4). To date, Pm is thought to be a strong swarmer cell among Proteus species and here two isolates, 91 1 and 91 2 , of Pm exhibited faster swarming ( Figure 4B,C) than other species resembling with other reports [28]. However, in this study we found an isolate of Ph (66 2 ) which showed strong swarming motility comparable to Pm (Figure 6 B,C,E).…”
Section: Kinetics Of Swarming Motilitycontrasting
confidence: 55%
“…For a precise and synthetic description of Proteus mirabilis swarm phenomenon, we refer to Rauprich et al [38] and Matsuyama et al [33]. Among all aspects described in those references, periodic alternation of swarm phases and of consolidation phases, without any motion, seem to be the most typical one.…”
Section: Introductionmentioning
confidence: 99%
“…This alternation gives rise to terraces as a resulting effect. The second one concerns the cell size distribution and was pointed out in Matsuyama et al [33]. As for space distribution at a given time, the swarming front is essentially constituted by long cells and the proportion of shorter cells grows while moving towards the colony interior.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations